Counseling on the Use of Lime (Citrus aurantifolia) as Pharmaceutical Preparations in the Making of Mouthwash and hand Sanitizer - H. Ambo Lau, Sulfiyana; Herman, Herman; Zulfiah, Zulfiah (Journal Pengabdian Masyarakat Politeknik Sandi Karsa, 2023)
Health services, including in the form of health counselling and traditional medicine, are one of the most elementary health service programs considering the level of the ratio of the population to the centre, health service units and health workers who do not meet the ideal balance, so a breakthrough and smart steps are needed in responding to this. I was counselling on the Use of Lime (Citrus aurantifolia) as a Pharmaceutical Preparation in the Making of Mouthwash (Mouthwash) and Hand Sanitizer  (  Antibacterial Hand Sanitizer) with the aim of improving the degree of health in the mouth and using Lime as a hand sanitiser. The methods of these activities are identification of the target objectives of the training, tools and materials used, good communication methods that are easy to understand, visualisation, evaluation, and feedback so that it can be concluded that counselling on the use of Lime as a pharmaceutical preparation in the manufacture of Mouthwash and Hand Sanitizer is a concern for healthy living in the surrounding community for the better. Thus creating a healthy and prosperous society.